Hypoxia Induces Saturated Fatty Acids Accumulation and Reduces Unsaturated Fatty Acids Independently of Reverse Tricarboxylic Acid Cycle in L6 Myotubes - Vacek, Lukas; Dvorak, Ales; Bechynska, Kamila; Kosek, Vit; Elkalaf, Moustafa; Trinh, Minh Duc; Fiserova, Ivana; Pospisilova, Katerina; Slovakova, Lucie; Vitek, Libor; Hajslova, Jana; Polak, Jan (Frontiers in Endocrinology, 2022)
Obstructive sleep apnea syndrome, characterized by repetitive episodes of tissue hypoxia, is associated with several metabolic impairments. Role of fatty acids and lipids attracts attention in its pathogenesis for their metabolic effects. Parallelly, hypoxia-induced activation of reverse tricarboxylic acid cycle (rTCA) with reductive glutamine metabolism provides precursor molecules for de novo lipogenesis. Gas-permeable cultureware was used to culture L6-myotubes in chronic hypoxia (12%, 4% and 1% O2) with 13C labelled glutamine and inhibitors of glutamine uptake or rTCA-mediated lipogenesis. We investigated changes in lipidomic profile, 13C appearance in rTCA-related metabolites, gene and protein expression of rTCA-related proteins and glutamine transporters, glucose uptake and lactate production. Lipid content increased by 308% at 1% O2, predominantly composed of saturated fatty acids, while triacylglyceroles containing unsaturated fatty acids and membrane lipids (phosphatidylcholines, phosphatidylethanolamines, phosphatidylinositol) decreased by 20-70%. rTCA flux of malate, citrate and 2-hydroxyglutarate increased by 4.7-fold, 2.2-fold and 1.9-fold in 1% O2, respectively. ATP-dependent citrate lyase inhibition in 1% O2 decreased lipid amount by 23% and increased intensity of triacylglyceroles containing unsaturated fatty acids by 56-80%. Lactate production increased with hypoxia. Glucose uptake dropped by 75% with progression of hypoxia from 4% to 1% O2. Protein expression remained unchanged. Altogether, hypoxia modified cell metabolism leading to lipid composition alteration and rTCA activation.